Translanguaging in Indonesian EFL Teacher Education: Meaning-Making and Pedagogy - Fakry Hamdani; Rully Agung Yudhiantara (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2026)
Despite the multilingual realities of EFL classrooms, English language teaching in many contexts continues to be influenced by monolingual ideologies that limit the recognition of multilingual practices in learning and teaching. Limited research has examined how translanguaging practices support meaning-making and pedagogical development among preservice teachers in Indonesian EFL teacher education contexts. This study examined translanguaging practices among preservice English teachers in an Indonesian EFL teacher education context, focusing on how these practices supported meaning-making and shaped pedagogical orientations. A qualitative case study design was employed involving 30 undergraduate students enrolled in a Sociolinguistics course. Data were collected through reflective narratives and semi-structured interviews and analyzed using thematic analysis. The findings indicated that translanguaging functioned as a dynamic and strategic resource in three main ways: facilitating conceptual understanding of complex content, sustaining interaction and participation during communication, and supporting the development of inclusive pedagogical perspectives. Participants flexibly used Indonesian and English to bridge linguistic gaps, maintain communicative flow, and enhance comprehension. The findings also showed that translanguaging contributed to shifts in language ideology, with participants increasingly viewing multilingual practices as legitimate and pedagogically valuable. This study highlights the importance of integrating translanguaging-oriented approaches into teacher education programs to promote more inclusive, context-responsive, and equitable English language teaching.